2014
DOI: 10.1111/ggi.12190
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a predictor of all-cause mortality in older men and women

Abstract: Frailty is strongly associated with higher mortality, especially among women. Among men, the association was explained by baseline functional capacity, comorbidity and lifestyle factors. Changes in frailty status should also be taken into consideration when planning geriatric care, as such changes could indicate a more rapid decline in health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 17 publications
7
88
1
5
Order By: Relevance
“…Sixteen articles corresponded to population-based longitudinal studies 18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Of these studies, one was a review and meta-analysis 36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen articles corresponded to population-based longitudinal studies 18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Of these studies, one was a review and meta-analysis 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, one was a review and meta-analysis 36 . Thirteen studies used the frailty phenotype as an operational model 18,[21][22][23][24][25][26][30][31][32][33][34]36 and four used the frailty index [27][28][29]35 . In studies that used the frailty phenotype the samples ranged from 654 to 6724 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the type of frailty scale used to assess participants is unlikely to entirely explain the variability of results. Even so, studies using the same approach to frailty assessment have yielded inconsistent results (Berges et al, 2009;Kulmala et al, 2014), which may indicate subtle differences in the operationalization of a frailty tool. Alternatively, variation across studies may be due to differences in study sample characteristics, such as life-stage (e.g., middle-aged versus old-age) (Saum et al, 2014), disability prevalence (Kulminski et al, 2006), country-of-origin and ethnicity.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Others have found that females tolerate frailty better, as evidenced through lower mortality rates at any given frailty score (Berges et al, 2009;Mitnitski et al, 2004). However, the male-female health-survival paradox has not been a consistent finding across all frailty studies (Berges et al, 2009;Kulmala et al, 2014;Kulminski et al, 2008;Kulminski et al, 2006;Puts et al, 2005;Saum et al, 2014). The variable results may reflect…”
Section: Introductionmentioning
confidence: 98%
“…3,4 Previous publications reported that frail people are at higher risk of age-related diseases and higher late-life mortality. [4][5][6] Over the past decade, several approaches have been proposed to define and evaluate frailty. 1,7,8 A widely accepted approach proposed by Mitnitski et al uses a continuous frailty index (FI) to define frailty as the proportion of accumulated health deficits, such as specific diseases, symptoms, signs, or disabilities presented at the time of investigation.…”
Section: Introductionmentioning
confidence: 99%